2011
DOI: 10.1016/j.jcrs.2010.08.043
|View full text |Cite
|
Sign up to set email alerts
|

Visual outcomes and optical performance of a monofocal intraocular lens and a new-generation multifocal intraocular lens

Abstract: The new-generation multifocal IOL restored distance, intermediate, and near visual function after cataract surgery. The optical quality with this type of IOL was particularly affected by IOL tilt and decentration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
90
0
13

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 148 publications
(108 citation statements)
references
References 49 publications
5
90
0
13
Order By: Relevance
“…8 In fact, both Muñoz et al 7 and Alió et al [8][9][10] reported that contrast sensitivity in MPlus-implanted patients was similar to that in monofocal IOL-implanted patients at any spatial frequency. [7][8][9][10] Moreover, Alió et al 9,10 reported that eyes implanted with an MPlus MIOL registered higher contrast sensitivity than did eyes implanted with a diffractive MIOL. This feature might also contribute especially for good distance vision, 7 and the immediate visual rehabilitation shown in our results at 1 day postoperatively.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…8 In fact, both Muñoz et al 7 and Alió et al [8][9][10] reported that contrast sensitivity in MPlus-implanted patients was similar to that in monofocal IOL-implanted patients at any spatial frequency. [7][8][9][10] Moreover, Alió et al 9,10 reported that eyes implanted with an MPlus MIOL registered higher contrast sensitivity than did eyes implanted with a diffractive MIOL. This feature might also contribute especially for good distance vision, 7 and the immediate visual rehabilitation shown in our results at 1 day postoperatively.…”
Section: Discussionmentioning
confidence: 97%
“…[7][8][9][10] Of the 11 patients, all were completely independent of spectacles for distance vision. For near vision, one patient needed to use eyeglasses occasionally, and one patient needed to use eyeglasses constantly.…”
Section: Preoperative Baseline Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a refractive multifocal IOL with rotational asymmetry has been developed and introduced into clinical practice. Their performance is being evaluated and compared with already existing IOL designs [37][38][39]. A diffractive multifocal IOL uses the base lens curvature and the zero and first diffraction orders to simultaneously produce the two focal points [40], [41].…”
Section: Model Eyes For Iol Testingmentioning
confidence: 99%
“…There is a great interest to determine either in a test bench [43], [44] or in clinical studies [45], [46] the conditions and the degree to which the aspheric design in apodized diffractive multifocal IOLs might be advantageous versus a conventional spherical design, particularly when some studies have shown little or no benefit of aspheric IOLs with small pupils [47, [48]. For the assessment of the optical performance of multifocal IOLs, the common metrics (point spread function, modulation transfer function, and visual acuity) have to be measured [38], [49][50][51][52] and also its behaviour in terms of the energy balance between the distance an near images and its variation with the pupil diameter. Very recent studies carried out in an optical bench show a discrepancy between the theoretical prediction of the design and the experimentally measured energy distribution between the two foci in apodized diffractive multifocal IOLs [53].…”
Section: Model Eyes For Iol Testingmentioning
confidence: 99%